Effect of post-deposition annealing on the growth and properties of cubic SnS films. (March 2017) - Chalapathi, U.; Poornaprakash, B.; Park, Si-Hyun
Abstract: We report a detailed investigation of the effect of post-deposition annealing on the growth and physical properties of chemically grown cubic SnS films. Chemically deposited cubic SnS films were subjected to annealing in a graphite box with loaded elemental sulfur under N2 at 150−350 °C for 10, 30, and 60 min in order to understand the grain growth and morphology of the films. Films annealed at 150−250 °C for 10 min showed improved grain size and a more uniform grain morphology. Films annealed at 150−250 °C for 30 and 60 min showed a decrease in the grain size and non-uniform grain morphology for the cubic SnS phase. Films annealed at 300 and 350 °C for 10 min revealed the formation of minor secondary phase SnS2, and the grain morphology changed from round shape to flake-like. Longer annealing at 300 and 350 °C improved the extent of the SnS2 phase, and it was found to be the dominant phase after annealing at 350 °C for 60 min. The direct optical band gap of SnS films is 1.75−1.67 eV, depending on the annealing temperature and time. The films exhibited p-type electrical conductivity. The films annealed at 250 °C for 10 min showed a higher hole mobility of 77.7 cm 2 V −1 s −1 . Thus, lower annealing temperatures and shorter annealing times are favorable conditions to produce high-quality cubic SnS films. Highlights: Post-deposition annealing showed significant effect on the growth of cubic SnS films. Annealing these films below 300 °C for shorter time of 10 min resulted good grain growth. SnS2 secondary phase formation observed at 300 °C even for 10 min of annealing.